HOMOGENEOUS ZONES OF SOIL PROPERTIES FOR IRRIGATION MANAGEMENT IN A VINEYARD - Nascimento, Patricia dos Santos [UNESP]; Silva, Juliano Athayde; Silva Costa, Bruno Ricardo; Bassoi, Luis Henrique (Soc Brasileira De Ciencia Do Solo, 2014)
In analysis of the spatial and temporal variability of the factors inherent to agricultural production, geostatistics is the basis for the application of the concepts of precision agriculture. Thus, this study was developed to evaluate the spatial variability of soil physical and water properties and to delineate homogeneous zones in a vineyard using geostatistical tools. A field experiment was carried out in Petrolina, Pernambuco, Brazil (in the Lower Middle Sao Francisco Valley) in a grape vineyard, irrigated by microsprinklers. In a 3.2 ha area, 160 soil samples were collected in the 0.0-0.20 and 0.20-0.40 m layers, in four transects, which were used for determination of soil particle size fractions (total sand, silt, and clay), the soil water retention curve, soil bulk density, and total porosity. Data were subjected to descriptive statistical analysis and geostatistical analysis, and spatial variability of the physical and water properties were observed. Interpolation by kriging was then performed, and contour maps were generated to delimit homogeneous soil zones. Soil bulk density, total porosity, and total sand showed low heterogeneity, while silt and clay showed medium heterogeneity. The spatial dependence index observed was classified from moderate to strong for all properties. The water available in the 0.20-0.40 m soil layer showed the greatest range, and it was the property considered for delimitation of three homogeneous zones, which received different amounts of irrigation water throughout two growing seasons in accordance with the soil moisture measured in each one of these zones.
Keywords: available soil water; geostatistics; spatial dependence